The Causality of Financial Inclusion and Economic Growth in Indonesia - Purwiyanta, Purwiyanta; Pujiharjanto, Ambar; Astuti, Rini Dwi; Kijkasiwat, Ploypailin (Jurnal Analisis Bisnis Ekonomi, 2022)
Sustainable economic growth has become one of the economic goals of concern for policymakers around the world. Financial inclusion has received significant attention in planning strong policies to achieve growth goals. This study aims to analyze how fast the response to economic growth is due to shocks to financial depth, financial access, and financial stability in 34 provinces in Indonesia, 2014-2019. This study uses vector auto-regression (VAR) models and Granger causality to test the main research questions. The results of the study show that financial depth and stability can promote growth, not vice versa. The existence of shocks to the three financial inclusion variables responded differently to economic growth.